Activation of Gcn2 in response to different stresses. - Silje Anda; Róbert Zach; Beáta Grallert (PLoS ONE)
All organisms have evolved pathways to respond to different forms of cellular stress. The Gcn2 kinase is best known as a regulator of translation initiation in response to starvation for amino acids. Work in budding yeast has showed that the molecular mechanism of GCN2 activation involves the binding of uncharged tRNAs, which results in a conformational change and GCN2 activation. This pathway requires GCN1, which ensures delivery of the uncharged tRNA onto GCN2. However, Gcn2 is activated by a number of other stresses which do not obviously involve accumulation of uncharged tRNAs, raising the question how Gcn2 is activated under these conditions. Here we investigate the requirement for ongoing translation and tRNA binding for Gcn2 activation after different stresses in fission yeast. We find that mutating the tRNA-binding site on Gcn2 or deleting Gcn1 abolishes Gcn2 activation under all the investigated conditions. These results suggest that tRNA binding to Gcn2 is required for Gcn2 activation not only in response to starvation but also after UV irradiation and oxidative stress.